2020
DOI: 10.1002/adhm.202000092
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Surface Engineering: Growth of Layered Double Hydroxides with Intrinsic Oxidase‐Mimicking Activities to Fight Against Bacterial Infection in Wound Healing

Abstract: Colloidal surface engineering is of particular importance to impart modular functionalities to the colloidal systems. Here, a layer of Mn/Ni layered hydroxides (Mn/Ni(OH)x LDHs) can be successfully coated on various colloidal particles, such as silica spheres, silica rods, ferrite nanocrystal supraparticles, as well as FeOOH nanorods. Such layered hydroxides have intrinsic oxidase‐mimetic activities, as demonstrated by catalytic oxidation of tetramethyl benzidine in the presence of oxygen. Furthermore, Mn/Ni(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Such findings come in line with those of Wang et al who reported the enhancement of lysosomal antibacterial function by loading lysozyme at the surface of ternary MgZnAl LDHs due to the rough surface of the host LDH providing better contact with bacteria and thus an amplified antibacterial effect [71]. Although these investigations suggest that the rough surface of LDHs aid in the adhesion phenomena leading to the achieved antibacterial effect [50,71], real measurements of LDH surface roughness are lacking. One good method to ensure the effectiveness of LDHs roughness in the antibacterial activity is to compare the antibacterial activity of different LDH samples having different surface roughness which could be evaluated easily by atomic force microscopy (AFM) for example [75,76].…”
Section: Topological Adhesion Of Ldh On Bacteriasupporting
confidence: 84%
See 4 more Smart Citations
“…Such findings come in line with those of Wang et al who reported the enhancement of lysosomal antibacterial function by loading lysozyme at the surface of ternary MgZnAl LDHs due to the rough surface of the host LDH providing better contact with bacteria and thus an amplified antibacterial effect [71]. Although these investigations suggest that the rough surface of LDHs aid in the adhesion phenomena leading to the achieved antibacterial effect [50,71], real measurements of LDH surface roughness are lacking. One good method to ensure the effectiveness of LDHs roughness in the antibacterial activity is to compare the antibacterial activity of different LDH samples having different surface roughness which could be evaluated easily by atomic force microscopy (AFM) for example [75,76].…”
Section: Topological Adhesion Of Ldh On Bacteriasupporting
confidence: 84%
“…One other possible reason explaining LDH-bacteria adhesion is the rough surface of LDHs thus promoting the adhesion phenomena which may be a key factor contributing to their antibacterial activity [50,71]. In fact, it had been well known that the motility of bacteria is essential for bacterial normal functions [72], and that rough antimicrobial colloidal surfaces might adhere to bacteria and disturb its normal motility functions [73].…”
Section: Topological Adhesion Of Ldh On Bacteriamentioning
confidence: 99%
See 3 more Smart Citations